Efficacy of Phloroglucinol Versus Placebo on the Duration of Labour in Term Pregnancies - Noreen Majeed, Shamsa Tariq (Journal of Rawalpindi Medical College, 2013)
phloroglucinol in terms of duration of first stage of labour Methods: In this randomized, controlled trial patients were divided into two groups as group A (phloroglucinol drug) and group B ( placebo). Sixty one patients in the drug group received phloroglucinol 40mg (4ml) I/V at >3cm dilatation Sixty one in the placebo group recieved distilled water 4ml I/V at >3cm dilatation. Dose was repeated after 60 min. Maximum 3 doses were given. Half hourly monitoring of vital signs, uterine contractions and fetal heart rate was done. Labour progress was plotted on partograph. Result:Mean gestational age in both groups was 38.8 weeks.The mean duration of the observed active phase of 1st stage of labour in drug group was 183 mins and 316 mins in placebo group. The mean duration of 2nd stage of labour in drug group was 25.16 mins and 34.52 mins in placebo group.The mean duration of 3rd stage of labour in drug group was 8.72 mins and 11.1 mins in placebo group.The mean total duration of labour in drug group was 216.88 mins and 358.52 mins in placebo group. Conclusion: Phloroglucinol is effective in reducing duration of first stage of labour